Group work and the change of obstacles over time: The influence of learning style and group composition. (July 2017) - Soetanto, Danny; MacDonald, Matthew
It is through working in groups that students develop cooperative learning skills and experience. However, group work activity often leads students into a difficult experience, especially for first-year students who are not familiar with group work activities at university. This study explores obstacles faced by first-year students during their group work activities. It investigates whether a group of students with a similar learning style (homogeneous group) experience different obstacles compared to a group of students with a diverse learning style (heterogeneous group). In addition, to identify the difference, if any, between a group formed by a tutor and one where the students form the group themselves, tutor and self-allocated group allocations are explored. This study focuses on obstacles experienced by these students during group work activities. Using a sample of more than 200 students over a period of 3 years, the types and the changes of obstacles in different stages of group life are explored. The findings show that students experience obstacles which can be classified into personal and social, leadership and management, and task-related obstacles. Those obstacles were not static but increased over time. The study also investigates the impact of different methods of forming groups and whether this impacted on obstacles experienced. Overall, different interventions prompted different patterns of obstacle development.